The lexicographic decision function - Dombi, József; Vincze, Nándor (Acta Cybernetica, 2005)
In this paper the lexicographic decision process is presented in a unified way. We construct a lexicographic decision function using a universal preference function and a unary function. This construction incorporates the different outranking approaches, the lexicographic decision process and the utility based decision making models. Finally we consider the connection of the lexicographic decision method and the Arrow paradox.